EXPERIMENTAL INVESTIGATION OF SUPER-CAPACITOR PERFORMANCE FOR ADVANCED ENERGY STORAGE APPLICATIONS - Muhammad Farhan Amjad; Abdul Jabbar; Muhammad Huzaifa; Muhammad Atif Imtiaz; Aiman Azhar; Shah Wali Ullah (Spectrum of Engineering Sciences, 2025)
Introduction: Super-capacitors are becoming promising alternatives to traditional energy hosts, with their high-power density, fast charge-discharge ability, and long cycle life (up to 106 cycles). In this research work, the electrochemical performance of hybrid graphene–transition metal oxide (TMO) electrodes was explored for advanced energy storage applications. Drop- casting and chemical vapor deposition were used for electrode fabrication, and ionic liquid-based electrolytes were introduced to increase stability and conductivity. Device performance was subjected to electrochemical characterization techniques such as cyclic voltammetry (CV), galvanostatic charge-ischarge (GCD), and electrochemical impedance spectroscopy (EIS). The results revealed a high specific capacitance of 950 F/g at low internal resistance (0.32 Ω) and superior cycling stability, less than 5% capacitance loss after 100,000 cycles. Compared to lithium ion batteries, super-capacitors have a much-however power density (800 W/kg) and lower energy density. Testing conductivity at varying temperatures confirmed stable performance at elevated temperatures (– up to 80 °C), making it a candidate for high-power applications such as electric vehicles and grid storage. Nonetheless, challenges related to scalability and cost-efficient fabrication persist, requiring further investigation in advanced material engineering and real-life evaluations. The study showcased the promise of graphene-TMO super-capacitors as next-generation energy storage technology, while also calling for further work in electrolyte optimization and the architectural boosting of energy density and practicability.